2004
DOI: 10.1021/ol047812a
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Hydrogen Bond Strength and pKa Determination of N,N‘-Disubstituted Imidazole-4,5-dicarboxamides

Abstract: N,N'-Disubstituted imidazole-4,5-dicarboxamides (I45DCs) form an intramolecular hydrogen bond worth an estimated 14 +/- 1 kcal/mol, as measured with a model structure in DMSO-d6 at 3 mM, thereby predisposing the molecular conformation to a folded rather than extended form. The I45DCs also show evidence of aggregation in both CDCl3 (>1 mM) and DMSO-d6 (>10 mM) solutions. These compounds are uncharacteristically weak bases in comparison with imidazoles bearing similar electron-withdrawing groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 15 publications
3
24
0
Order By: Relevance
“…Amino acid side chains are natural recognition elements in substrate-enzyme, ligand-receptor, and protein-protein interactions, and we have shown that I45DCs form a strong intramolecular hydrogen bond that remains stable even in water at pH 7 [15]. Moreover, the strong intramolecular hydrogen bond anticipated in each of these I45DCs accomplishes three important tasks: it predisposes the amino acid ester substituents to be separated by a distance comparable with side chain separations found adjacent on one side in an α-helix or on one side in a β-strand secondary structure [12,16], yields a quasi ring that combines with the imidazole to yield mimics of substituted purines [13,16], and offers added low-energy conformational flexibility for the compound to adapt to the binding site, which is an advantage over an all covalently bonded scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Amino acid side chains are natural recognition elements in substrate-enzyme, ligand-receptor, and protein-protein interactions, and we have shown that I45DCs form a strong intramolecular hydrogen bond that remains stable even in water at pH 7 [15]. Moreover, the strong intramolecular hydrogen bond anticipated in each of these I45DCs accomplishes three important tasks: it predisposes the amino acid ester substituents to be separated by a distance comparable with side chain separations found adjacent on one side in an α-helix or on one side in a β-strand secondary structure [12,16], yields a quasi ring that combines with the imidazole to yield mimics of substituted purines [13,16], and offers added low-energy conformational flexibility for the compound to adapt to the binding site, which is an advantage over an all covalently bonded scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously observed two intramolecularly hydrogen bonded conformations in dissymmetrically-disubstituted I45DCs and provided evidence that the favored hydrogen bond donor arose from increasing substitution adjacent the amide nitrogen 38. Moreover, we have shown in model I45DCs that the intramolecular hydrogen bond is relatively strong and worth least 14±1 kcal/mol, as well as observed in an aqueous environment 39. The two conformations for 22 { 2,1,3,2 } shown in Figure 2 are therefore real possibilities for explaining the observed behavior in both the LC-MS analysis and 1 H NMR spectra.…”
Section: Resultsmentioning
confidence: 63%
“…We know from our previous experience with monomeric derivatives that self-association occurs at or above 1 mM in CDCl 3 and above 10 mM in DMSO- d 6 39. Thus, VT-NMR was performed from 30 °C to 70 °C in DMSO- d 6 for 22 { 2,1,2,2 } and 22 { 2,1,3,2 } at 3 mM (see supporting information), resulting in similar 1 H NMR spectra observed for both compounds across the range of temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen bonding is particularly significant to the study on the molecular recognition in the living organism [6,7]. Hence, an increase in interest by scientists in hydrogen bonding was aroused [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Inouye et al [6] proved that the multi-pyridine macrocyclic acceptor could recognize a furan nucleotide via hydrogen bonds, and determined the stabilization constant as well as thermodynamic parameters. The strength of the intra-molecular hydrogen bond and stability of oligomers formed by inter-molecular hydrogen bonds were discussed by Rush et al [7]. Recent research indicated that the hydrogen bonds formed by nitrobenzene in the reduced state in the presence of arylureas could be broken down in the oxidized state so that a fast redox molecular "On-off" switching was made [8].…”
Section: Introductionmentioning
confidence: 99%